Improvised Marketing Interventions in Social Media. (March 2020) - Borah, Abhishek; Banerjee, Sourindra; Lin, Yu-Ting; Jain, Apurv; Eisingerich, Andreas B.
Online virality has attracted the attention of academics and marketers who want to identify the characteristics of online content that promote sharing. This article adds to this body of research by examining the phenomenon of improvised marketing interventions (IMIs)—social media actions that are composed and executed in real time proximal to an external event. Using the concept of quick wit, and theorizing that the effect of IMIs is furthered by humor and timeliness or unanticipation, the authors find evidence of these effects on both virality and firm value across five multimethod studies, including quasiexperiments, experiments, and archival data analysis. These findings point to the potential of IMIs in social media and to the features that firms should proactively focus on managing in order to reap the observed online sharing and firm value benefits.